New species of the damselfly genus Argia from Mexico, Central America and Ecuador with an emphasis on Costa Rica (Insecta: Odonata: Coenagrionidae) - Garrison, Rosser W.; Ellenrieder, Natalia Von (Zootaxa, 2017)
Seven new species of Argia are described, five of which occur in Costa Rica: Argia calverti n. sp. (Holotype ♂, Costa Rica, Cartago Prov., Tapantí Reserve, 1,310 m, 6 vii 1963, F. G. Thompson leg., in FSCA); Argia carolus n. sp. (Holotype ♂, Costa Rica, San José Prov., El Rodeo Biological Reserve, 7 km W of Villa Colón, 9°54’ N, 84°16’ W, 561 m, 10–13 vii 1990, T. W. Donnelly leg., in FSCA); Argia elongata n. sp. (Holotype ♂, Costa Rica, Cartago Prov., Reventazón river, SE of Turrialba by highway 10, 9°52’56’’ N, 83°38’49’’ W, 561 m, 10 viii 1979, R. W. & J. A. Garrison leg., in CSCA); Argia haberi n. sp. (Holotype ♂, Costa Rica, San José Prov., Bosque del Tolomuco, km 118 on Pan American highway, in seeps and trickles through brushy pasture on forested hillside, 9°28’18’’ N, 83°41’48’’ W, 1,710 m, 27 iii 2006, F. Sibley leg., in FSCA); Argia schorri n. sp. (Holotype ♂, Costa Rica, Puntarenas Prov., 2.8 mi E of Golfito, 8°39’ N, 83°7’ W, 35 m, 4 vii 1967, O. S. Flint, Jr. & M. A. Ortiz B. leg., in USNM), and two which are so far only known from Mexico and Ecuador respectively: Argia rudolphi n. sp. (Holotype ♂, Mexico, Puebla State, Zihuateutla, Sierra de Huauchinango, La Unión, in drainage area, 20°14’25’’ N, 97°53’38’’ W, 596 m, 21 v 1987, R. Novelo & A. Gómez leg., in CSCA) and Argia schneideri n. sp. (Holotype ♂, Ecuador, Napo Prov., Las Palmas, on Anzu river in Napo river watershed, 11 xii 1936, W. Clark-MacIntyre leg., in UMMZ). All the new species, as well as closely related species needed for diagnosis including A. anceps Garrison, A. cupraurea Calvert, A. cuprea (Hagen), A. extranea (Hagen), A. fissa Selys, A. fulgida Navás, A. oenea Hagen in Selys, A. popoluca Calvert, A. rhoadsi Calvert, and A. westfalli Garrison, are illustrated and diagnosed from their congeners and their known distribution areas are mapped.